APLIKASI TEORI PSIKOLOGI BELAJAR ABRAHAM MASLOW DALAM PENGEMBANGAN ORGANISASI KERJA Di CV. KANCA YUSPITA MEDAN - Yusmariono Yusmariono (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Applying some theory or idea of Maslow's theory of psychology, psychology of the company completely is not possible. However, what is the situation in which Maslow once led the Vendor, and then he became a researcher and expert in the science of the soul so much that can be recorded, made either by the principles of leadership, staff, workers in the organization of work of our company. The value of the full value of Maslow is his research on various mind others that success and found the traits characteristic of individuals who may be in various places, especially in the application of our company is the opinion of a very valuable and priceless. And the following quote is the end of the humanistic theory of Maslow application of this article.